Expressive Speech Acts Analysis of “Looking for Alaska” Novel by John Green - Galuh Virginia Elhamsyah; Ambalagin, Ambalegin (Asosiasi dosen IDEBAHASA KEPRI, 2023)
This descriptive qualitative research discovered the expressive acts in John Green's novel